Analisis Perbedaan Ketajaman Penglihatan Mata Kanan, Kiri, dan Binokular pada Remaja dengan Lama Paparan Gadget - Mikawati; Nofianti (Politeknik Baubau, 2026)
Visual acuity is an important indicator of visual function that may be affected by prolonged gadget use. This study aimed to analyze differences in visual acuity between the right eye, left eye, and both eyes based on the duration of gadget use among adolescents. This research employed an analytical observational design with a cross-sectional approach involving 77 adolescents aged 12–15 years selected using random sampling techniques. Data were collected through visual acuity examinations using a Snellen chart and questionnaires regarding gadget use duration. Data analysis was performed using the Mann–Whitney test to compare visual acuity based on gadget use duration groups, while Friedman and Wilcoxon tests were used to analyze differences in visual acuity between eyes in the group using gadgets for more than 4 hours per day. The results showed significant differences in visual acuity between adolescents with gadget use duration of ≤4 hours and >4 hours per day in the right eye (p=0.001), left eye (p<0.001), and both eyes (p=0.001). In addition, significant differences were also found between the right eye, left eye, and binocular visual acuity in the >4 hours/day group (p=0.025).In conclusion, prolonged gadget use is associated with decreased visual acuity and differences in visual function among adolescents. Therefore, controlling gadget use duration is important as a preventive effort to maintain adolescent eye health.